Pemetaan Penelitian Rasio Biaya Operasional terhadap Pendapatan Operasional (BOPO) pada Perbankan Syariah dan Konvensional: Studi Bibliometrik VOSviewer dan Literature Review - Eka Wahyu Hestya Budianto; Nindi Dwi Tetria Dewi (JAF (Journal of Accounting and Finance), 2023)
This study aims to determine the research mapping regarding the Operating Income to Operating Costs (OIOC) ratio in Islamic and Conventional Banking using a mix-method approach, namely the VOSviewer bibliometric study and literature review. Data analysis techniques include: (1) mapping the distribution of journal publications around the OIOC ratio; (2) mapping the results of the VOSviewer bibliometric visualization around the OIOC ratio based on the number of clusters and their items; and (3) mapping research topics around the OIOC ratio using a literature review study. The results showed that: (1) based on the distribution of journal publications, there were 736 journal publications regarding the OIOC ratio; (2) based on the mapping of the VOSviewer bibliometric study, the network visualization results around the OIOC ratio are divided into 4 clusters and 163 topic items; (3) based on the mapping of literature review studies, there are 49 topics around the influence of the OIOC ratio and 14 topics about the determinants of the OIOC ratio. The implications and contributions of this research are to map research topics around OIOC ratios in Islamic and Conventional Banking which are often or rarely researched by researchers so that they can be a reference for subsequent researchers. Keywords: Operating Income to Operating Costs (OIOC); Bibliometrics; VOSviewer; Literature Review; Islamic and Conventional Banking